Comparison of the seasonal patterns of asthma identified in general practitioner episodes, hospital admissions, and deaths. Issue 8 (1st August 2000) - Fleming, D M; Cross, K W; Sunderland, R; Ross, A M
Abstract : BACKGROUND: Seasonal variations in asthma are widely recognised. This study was undertaken to investigate the relative differences in seasonal patterns by age as they impact on episodes of care in general practice, hospital admissions, and deaths. METHODS: General practice episode data from the Weekly Returns Service of the Royal College of General Practitioners, hospital admissions for asthma in England, and deaths registered as due to asthma in England and Wales over the years 1990–7 were examined. Age specific weekly rates of new episodes of asthma presenting to general practitioners, numbers of hospital admissions and deaths were analysed by the multiplicative decomposition method to separate secular from seasonal trends. The seasonal indices thereby obtained were plotted as three week moving averages. RESULTS: In children aged 0–4 and 5–14 years general practice episodes and admissions to hospital were strikingly congruent in timing and in magnitude, except in September when particularly high rates of admission (absolute and relative to general practice episodes) occurred. In the 15–44 age group there were marked mid summer peaks of general practice episodes and deaths but admissions to hospital were at about the annual average; in September/October there were peaks of episodes and admissions whereas deaths peaked in November. In the 45–64 age group a peak in general practice episodes of asthma was evident in mid summer when admissions were about average and deaths were at a minimum; all three measures tended to increase gradually with the approach of winter. Finally, in those age over 65 years, general practice episodes of asthma, admissions to hospital, and deaths followed similar 'U' shaped patterns with substantial peaks in mid winter. CONCLUSIONS: The seasonal pattern of asthma evolves with age. There are important differences in the seasonal pattern of general practice episodes, admissions to hospital, and deaths. Individual seasonal histories are important for the management of asthma. The combined analysis of these three data sets provides a new perspective on the epidemiology of asthma.